Les Cours En Ligne de Production Écrite Intermédiaire À L’Aide de L’application de Discord : La Mise En Œuvre Et Réponse Des Étudiants - farhan, farhan; Purwani, Neli (Program Studi Pendidikan Bahasa Prancis, Fakultas Bahasa dan Seni, Universitas Negeri Semarang, 2021)
Abstract Discord est une application conÃƒÂ§ue pour aider les utilisateurs ÃƒÂ communiquer et ÃƒÂ coordonner via des serveurs privÃƒÂ©s qui permettent dÃ¢â‚¬â„¢envoyer des messages texte et des conversations vocales avec dÃ¢â‚¬â„¢autres utilisateurs. Le but de cette recherche est dÃ¢â‚¬â„¢obtenir la rÃƒÂ©ponse des ÃƒÂ©tudiants et de connaÃƒÂ®tre la mise en Ã…â€œuvre et lÃ¢â‚¬â„¢ÃƒÂ©valuation de lÃ¢â‚¬â„¢apprentissage en ligne dans les cours de production ÃƒÂ©crite intermÃƒÂ©diaire en utilisant lÃ¢â‚¬â„¢application discord. Cette recherche a utilisÃƒÂ© une approche descriptive qualitative-quantitative qui visait ÃƒÂ dÃƒÂ©crire un symptÃƒÂ´me social qui ÃƒÂ©tait en cours au moment de lÃ¢â‚¬â„¢ÃƒÂ©tude. Discord app nÃ¢â‚¬â„¢est pas une plate-forme pour lÃ¢â‚¬â„¢ÃƒÂ©ducation, mais il a des fonctionnalitÃƒÂ©s de canal de texte et de canal vocal qui peuvent aider ÃƒÂ lÃ¢â‚¬â„¢ÃƒÂ©tude des compÃƒÂ©tences dÃ¢â‚¬â„¢ÃƒÂ©criture (Production Ãƒâ€°crite IntermÃƒÂ©diaire Abstract Online learning is learning without direct face to face between teachers and students, but done online. In the course of Production Ãƒâ€°crit IntermÃƒÂ©diaire, lecturers use the Discord application as a platform that helps in online lectures. This research used a qualitative-quantitative descriptive approach that seeks to describe a social phenomenon that was underway at the time of the study. The instrument used to collect data is an open questionnaire. Data analysis is done with data tabulation which is to organize data in the form of tables and diagrams. The results of this research include in online learning students realize activeness by presenting on time, and actively asking questions. Elena's facilities are helpful but not yet optimal, because Elena is only used as a task collector and quiz. Respondents responded positively about the use of discord for writing or PEI skills lectures.